U.S. HUMAN RIGHTS ACTIVISM AND PLAN COLOMBIA - Winifred Tate (Universidad de Los Andes, 2009)
Non-governmental organizations claim to play a central role in defining U.S. foreign policy, particularly in the field of human rights. Here, I will examine the role of human rights andhumanitarian groups in the debates over U.S. foreign policy towards Colombia, focusing on the design and subsequent additional appropriations for Plan Colombia, a multi-billion dollar aid package beginning in 2000. I argue that NGOs were able to build on the legacy of prior human rights activism focusing on Latin America, but failed to achieve significant grassroots mobilization around this issue. I examine the structural issues limiting such mobilization, as well as exploring how NGOs did leverage legislative conditions placed on the assistance package to keep human rights concerns part of the debates over U.S. policy. This case study will contribute to the historical record of how policy is made and developed, adding to the growing literature exploring how human rights claims translate into specific governmental policies.